THE USE OF THE SUBMENTAL FLAP IN RECONSTRUCTION OF HEAD AND NECK DEFECTS - O. A. Saprina; R. I. Azizyan; V. Zh. Brzhezovsky; A. M. Mudunov; I. S. Romanov; G. F. Allakhverdiyeva; S. B. Alieva; M. V. Lomaya (Сибирский онкологический журнал)
Reconstruction of head and neck defects after surgery for cancer remains challenging. The choice of the reconstruction technique  depends on the tumor size and localization, type of the defect,  patient’s age, concomitant diseases, and disease prognosis.  Surgeons have currently a broad range of material for reconstructive surgery, from free flaps to revascularized flaps. Microsurgical  reconstruction has made a revolution in treatment of patients with  complex head and neck defects. However, the use of this technique may not be advisable for some patients. The search for  new techniques is needed to improve functional and aesthetic results and reduce traumatism without compromising oncologic outcomes.  Thirty-six patients underwent surgery with reconstruction using the  submental island flap, a new alternative in the reconstruction of  various head and neck defects. The graft was taken after making a  neck incision for neck lymph node dissection. A few patients develop  total and marginal necrosis of the graft. Short- and long-term results showed no worsening of oncologic outcomes in the selected group of patients.